Peningkatan Pengetahuan dan Perilaku Gizi Seimbang menggunakan Metode Peer Education - Permatasari, Tria Astika Endah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Balanced nutritional behavior is consume any type of food containing nutrients in accordance with the needs of the body affect the nutritional status and health of the elderly. In Indonesia, knowledge and behavior that is principled on the four pillars of food diversity, clean living behavior and maintain a normal weight is still low. The objective of the study was to prove the improvement and the behavior of balanced nutrition after educational intervention with peer education method. Method: The study was an experimental quasi-study design. The study was conducted in March-July 2016 in South Tangerang City. A sample of this research is 98 elderly women who received education by peer education method, which is studying balanced nutrition in small groups (6-8 elderly per group). A total of 49 Elders came from two Posbindu in Kranggan (Dahlia and Kenanga) as intervention groups and 49 elderly from two Posbindu at Ciputat (Rambutan and Alpukat) as a control group. Paired t test is used to know the change of knowledge value and nutrition behavior in both groups. Results: There was a significant increase (p = 0.048) on average knowledge scores before and after intervention in the intervention group. The mean score of knowledge before intervention was 64.5 ± 24.9 SD and the mean knowledge score after intervention was 70.5 ± 22.6 SD. Balanced nutritional behavior increased from seven balanced nutritional behaviors, averaging only three categories of behaviors pre-intervened. Behavior increases with an average of four categories of balanced nutritional behavior performed. There was no increase in knowledge and behavior of balanced nutrition in the control group. Conclusion: The method of peer education can improve the knowledge and behavior of balanced nutrition in the control group. Balanced nutrition education needs to be socialized with a broader peer education method in the community.Keywords: elderly, peer education, balanced nutrition behavior, elderly nutrition.